CAMD: a switch migration based load balancing framework for software defined networks. Issue 4 (1st July 2019) - Sahoo, Kshira Sagar; Sahoo, Bibhudatta
Abstract : Software defined networks (SDN) and OpenFlow (OF) technologies have brought a new form of network architecture that simplifies the network management through innovations and programmability. The controller of SDN architecture has an abstract view of the entire network that smoothly handles the underlying hardware devices. In SDN, the control messages (e.g. packet_in ) arriving at the controller have the highest contribution of the controller's load. Upon exceeding a certain threshold of these messages, the response time of the controller increases due to the over memory and CPU utilisation. In this respect, the balancing of control messages is essential. To balance this control messages, migration of OF switches from an overloaded controller to an underloaded controller is a viable solution. However, such migration process has to perform with a well‐designed mechanism, failed to this the process might increase the response time of the control events. Taking this into account, the authors introduce controller adaption and migration decision (CAMD) framework, a switch migration based load balancing strategy, which effectively selects both switch and target controller such that it affects the response time minimally. This efficient switch migration technique ensures better load balancing with reduced response time and improved end‐user quality of services.